State-of-the-Art Digital Twin Applications for Shipping Sector Decarbonization - Bill Karakostas; Takis Katsoulakos (IGI Global, 2024)
The shipping industry, responsible for approximately 3% of global greenhouse gas emissions, urgently needs decarbonization to combat climate change. Traditional approaches to reducing emissions have yet to achieve significant, sustainable results. Maritime businesses and naval engineers need innovative solutions to meet ambitious emissions reduction targets and regulatory requirements. State-of-the-Art Digital Twin Applications for Shipping Sector Decarbonization offers a groundbreaking solution to the challenges of shipping decarbonization. By focusing on integrating digital twin technologies, this book presents a new paradigm for enhancing operational efficiency, reducing environmental impact, and meeting regulatory compliance. Through digital twins, maritime businesses can gain valuable insights into their operations, optimize energy consumption, and develop sustainable practices. State-of-the-Art Digital Twin Applications for Shipping Sector Decarbonization provides a state-of-the-art review of digital twin technologies and their applications in the shipping industry. The book covers various topics, from conceptual frameworks to practical implementations, including digital twin model representation, management, and applications in ship operations and design. It also explores the use of digital twins in the development of renewable technologies and installation onboard ships. By offering insights from EU-funded research and real-world case studies, this book is invaluable for researchers, naval engineers, and maritime professionals seeking to drive sustainability and innovation in the shipping industry.
Keywords: 380; Transport industries; Development economics and emerging economies